Passionate enquiry and school development : a story about teacher action research - Dadds, Marion (Falmer Press, 1995)
The main feature of this book is a case story of a teacher action researcher, Vicki, undertaking research in her own school as part of an Advanced Diploma course. The second important feature is this study grew out of Dr. Dadds' own action research on her in-service course with a group of primary and middle school teachers which included Vicki. The case story examines Vicki's three action research studies in turn; how they related to her work in the school; how she did her research; what problems she had to encounter; how she felt about her research and the people involved in it; what impact the research had on her feelings and ideas; and, what were some of the outcomes.